2000
DOI: 10.1161/01.hyp.35.3.775
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Calcium Antagonists on Glomerular Arterioles in Spontaneously Hypertensive Rats

Abstract: Abstract-Through the use of microanatomic techniques, we investigated the effects of treatment with some dihydropyridine-type calcium antagonists (CAs) (ie, lercanidipine, manidipine, and nicardipine) and with the nondihydropyridinetype vasodilator hydralazine on hypertension-dependent glomerular injury and on the morphology of afferent and efferent arterioles in spontaneously hypertensive rats (SHR). Fourteen-week-old male SHR and age-matched normotensive Wistar-Kyoto rats were left untreated (control groups)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
1
9

Year Published

2001
2001
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(40 citation statements)
references
References 24 publications
2
28
1
9
Order By: Relevance
“…32,40,44,47 This pharmacological profile is not universal, though: DHP CCBs, such as lercanidipine and manidipine, were recently shown to cause a similar degree of relaxation in pre-as in post-capillary renal vessels. 59 That same peculiar behaviour might also extend to the postural control of cutaneous microcirculation thus preserving more efficiently intracapillary pressures and perhaps engendering less fluid extravasation, a purely speculative hypothesis at this time.…”
Section: Discussionmentioning
confidence: 93%
“…32,40,44,47 This pharmacological profile is not universal, though: DHP CCBs, such as lercanidipine and manidipine, were recently shown to cause a similar degree of relaxation in pre-as in post-capillary renal vessels. 59 That same peculiar behaviour might also extend to the postural control of cutaneous microcirculation thus preserving more efficiently intracapillary pressures and perhaps engendering less fluid extravasation, a purely speculative hypothesis at this time.…”
Section: Discussionmentioning
confidence: 93%
“…Experimental studies have shown that lercanidipine also has a distinct vasodilatory effect on the efferent arteriole in addition to the afferent arteriole in the kidney. 13 Thus, it was stated that lercanidipine provides a more balanced pre-and postglomerular dilation, thereby reducing intracapillary pressure. It was hypothesized that such a balanced vasodilator action could take place in other capillary beds as well, which results in decreased incidence of the edema.…”
Section: Discussionmentioning
confidence: 99%
“…Эти важнейшие особенности поз-воляют не только успешно применять лерканидипин для лечения АГ у больных с протеинурией и хронической болезнью почек (ХБП), но и воздействовать на основ-ные показатели, определяющие почечную функцию [44].…”
Section: дополнительные эффекты лерканидипинаunclassified